HUBUNGAN TINGKAT EKONOMI KELUARGA DENGAN ANGKA PUTUS SEKOLAH DI KECAMATAN BAYAN KABUPATEN LOMBOK UTARA - Zulkarnain; Suharyani; M. Arief Rizka; Kholisussa'di (IKIP Siliwangi, 2026)
This study aims to determine the relationship between family economic status and dropout rates in Bayan District. This study employed a quantitative approach with a correlational method. The population comprised 65 families, with 15 respondents selected through purposive sampling. These respondents were low-income families with children who dropped out of school. The primary data collection instrument was a questionnaire, supported by interviews and documentation. Data analysis was conducted using the Pearson Product Moment correlation technique. The results of the study indicate a correlation between family economic status and school dropout rates, with a correlation coefficient of r = 0.48, which is considered moderate. This indicates that family economic conditions influence children's decisions to continue or discontinue their education, although it is not the sole determining factor. Other factors such as parental education level, the child's motivation to learn, the social environment, and access to education also influence dropout rates. Based on the results of this study, it can be concluded that family economic status has a significant relationship with the school dropout rate in Bayan District.